Transforming School Behavior Management: Integrating Positive Discipline within Educational Leadership Frameworks - Dian Evy Nofitasari; Akmal Mundiri (Al-Qalam Institue, 2026)
This study aims to examine the forms of student behavior management in schools and to explore how educational institutions transition from reactive disciplinary practices to positive, supportive approaches. Using a qualitative case study design, data were collected through interviews, classroom observations, and document analysis. The findings indicate five main strategies employed by teachers: stern reprimands, standing punishments, cleaning tasks, verbal appreciation, and praise. The first three represent traditional, reactive disciplinary methods that effectively manage immediate classroom disruptions but have limited impact on fostering long-term behavioral awareness. In contrast, verbal appreciation and praise reflect the initial implementation of positive reinforcement, promoting students’ confidence, responsiveness, and cooperation. The imbalance between punishment and reward practices highlights the lack of structured behavior management policies and the need for systematic educational management. The study concludes that schools are gradually shifting toward a more humanistic and proactive approach to behavior management. The implications emphasize the importance of clear written guidelines, teacher training to enhance competence in positive disciplinary strategies, and the development of a supportive school culture that integrates social-emotional learning and leadership principles to strengthen overall classroom management.